The challenges for new principals in the 21st century : developing leadership capabilities through professional support - Shoho, Alan R.; Barnett, Bruce G.; Tooms, Autumn K. (International research on school leadership, 2010)
This book series, International Research on School Leadership focuses on how present-day issues affect the theory and practice of school leadership. For this inaugural book, we focused on the challenges facing new principals and headteachers. Because the professional lives of school leaders have increasingly impinged on their personal well-being and resources have continued to shrink, it is important to understand how new principals or headteachers share and divide their energy, ideas, and time within the school day. It is also important to discover ways to provide professional development and support for new principals and headteachers as they strive to lead their schools in the 21st century. For these reasons, this book is dedicated to exploring the rarely-examined experiences of those who enter the role as new principals or headteachers.By giving voice to new principals and headteachers, we are able to determine what aspects of leadership preparation ring true and what aspects prove to be of little or no utility. Unlike leadership texts that have focused on conceptual considerations and personal narratives from the field, this book focuses on a collection of empirical efforts centered on the challenges and issues that new principals and headteachers experience during their initial and crucial years of induction. We solicited and accepted manuscripts that explore the multi-faceted dimensions of being a new principal or headteacher in the 21st century. Our goal was to create an edited book that examines the commonalities and differences that new principals and headteachers experience from an international perspective. This edited book is comprised of six chapters, each of which contributes a unique perspective on the responsibilities that new principals and headteachers are experiencing at the dawn of the 21st century.